Potential and development prospects of wind generation on the Kola Peninsula - N. G. Lyubimova; A. S. Flaxman; A. G. Redin; A. D. Kuchkina (Вестник университета)
Currently, qualified generating stations powered by renewable ener gy sources (hereinafter referred to as RES) are becoming increasingly popular in the electric power industry. Wind farms and solar generating panels have become mostly common in the modern world. Russia is a vast country that offers many potential locations for RES facilities. The аrctic zones attract special attention. However, having chosen a potential location for the construction of such an object, it is necessary to analyse the effectiveness and feasibility of the investment project. The purpose of this study is to consider the current state of the Murmansk region’s energy system for further determination of the probability of new energy projects developing there. In this regard, the wind energy potential of the region has been assessed, and the forecast of electricity consumption for the period from 2024 to 2029 has been performed. The authors have analysed justifications and possibilities for the construction of wind power plants on the territory of the Kola Peninsula as an alternative to stations powered by hydrocarbon fuels. It has been found that the existing opportunities in the Russian region are favourable for the realisation of new wind farm on its territory. A comparative analysis of the Murmansk region and neighboring territories has shown that this area is suitable for implementing such investment projects.